2016
DOI: 10.1193/053013eqs139m
|View full text |Cite
|
Sign up to set email alerts
|

On the Seismic Response of the Faculty of Architecture and Engineering Building at Tohoku University

Abstract: The Faculty of Architecture and Engineering Building at Tohoku University survived two strong ground motions. This is not surprising because the structure was stiff and strong. What is surprising is that the first ground motion did not cause severe structural damage but the second one caused so much structural damage that the building had to be evacuated and demolished. The damage occurred despite two key facts: (1) the intensities of the mentioned ground motions are understood to have been similar and (2) the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
(5 reference statements)
1
3
0
Order By: Relevance
“…In model A, which represented the expected behavior of the building after strengthening using results of this study, damage was most prominent in the third story boundary columns, with no damage above this story. This is consistent with what was observed in the field after the 2011 earthquake (Wang et al 2016).…”
Section: ) Model a Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…In model A, which represented the expected behavior of the building after strengthening using results of this study, damage was most prominent in the third story boundary columns, with no damage above this story. This is consistent with what was observed in the field after the 2011 earthquake (Wang et al 2016).…”
Section: ) Model a Resultssupporting
confidence: 92%
“…21. Based on the record of the accelerometer on the ninth floor, Wang et al (2016) the relationship between the acceleration and the displacement at the accelerometer and showed that the relationship included sudden decreases of the acceleration. The solid line in Fig.…”
Section: ) Model a Resultsmentioning
confidence: 99%
See 2 more Smart Citations